2016
DOI: 10.1007/s11365-016-0416-5
|View full text |Cite
|
Sign up to set email alerts
|

Network brokers or hit makers? Analyzing the influence of incubation on start-up investments

Abstract: Incubators are a prominent way to support technology based start-ups. Yet, it remains unclear to what extent these incubators enhance start-up performance, nor is it known through which mechanisms this would occur. In this paper we test two mechanisms to explain the relationship between incubation and the amount of investments raised by early stage start-ups as performance measure. The 'hit maker' mechanism refers to beneficial effects of the direct transfer of resources and organizational or business knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 78 publications
(144 reference statements)
0
15
0
4
Order By: Relevance
“…Several authors have emphasized the positive and statistically significant relationship between support mechanisms and the level of universities' entrepreneurial activity (Powers and McDougall ). Van Rijnsoever et al () found that incubators do have positive effects with respect attracting the amount of funding start‐up and the capacity to seek funding for banks and other formal investors. However, other studies of incubators have also found no effect or negative of incubators (Schwartz ).…”
Section: Understanding the Individual And University Determinants Of mentioning
confidence: 99%
“…Several authors have emphasized the positive and statistically significant relationship between support mechanisms and the level of universities' entrepreneurial activity (Powers and McDougall ). Van Rijnsoever et al () found that incubators do have positive effects with respect attracting the amount of funding start‐up and the capacity to seek funding for banks and other formal investors. However, other studies of incubators have also found no effect or negative of incubators (Schwartz ).…”
Section: Understanding the Individual And University Determinants Of mentioning
confidence: 99%
“…It has also been identified that the capability to connect start-ups to specific financial sources improves the factors important for incubators for increase their investments (Van Rijnsoever et al, 2017). It has also been found that participating in network events, engaging in referral services and the sheer fact of being linked to a reputable incubator puts the start-ups in a beneficial position, while supporting actions directly targeted at gaining more funding (such as pitch training) have less influence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In spite of that, it does not mean that the supporting actions correlated to hit-making, such as coaching, mentoring or workshops, are all in vain. The performance indicators related to raising funding are primarily applicable to new business players (Eveleens et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tenants' extensive involvement in multiple social and commercial networks can be a signal of tenants' growth potential, and diverse service providers are more willing to attach to tenants with such a signal [34]. Furthermore, the amount and attribution of relationships determine a tenant's capability to get tangible resource and intangible knowledge [35], thus the tenant's growth and successful graduation. Therefore, network involvement leads to heterogeneous mechanism of attachment, which impacts the positive relationship between entrepreneurial experience and TG.…”
Section: Moderating Effects Of Network Involvement On Entrepreneurialmentioning
confidence: 99%